พฤติกรรมผู้บริโภคในการซื้อผลิตภัณฑ์เสริมอาหารชนิดเม็ดในอำเภอเมืองเชียงใหม่ - ศุภชัย วังลัยคำ (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
This independent study aimed to investigate consumer behavior in buying tablet dietary supplement products in Mueang Chiang Mai district. Samples were specified to 280 adult consumers in the age of 21-60 years old, who purchased the tablet dietary supplement products in Mueang Chiang Mai district. Data was collected in according to the convenient sampling method with predetermined quota for age. The findings presented that most respondents were female in the age of 21-60 years old with Bachelor’s degree. They worked as private company employee whose average monthly income was ranked at the amount of 15,000-30,000 Baht and were single. Based upon the study on behavior of consumers in buying tablet dietary supplement products in Mueang Chiang Mai district, the results revealed that the majority of respondents consumed multi-vitamin and bought it for self-consumption. They preferred the products produced in Thailand and believed that the qualities of domestic and imported products were indifferent. Most of them consumed it in a form of capsule and bought it from drugstores with the frequency of once in over than 3 months. Reason in consuming this product was referred to their health-concerned habit. The most favorite brands of tablet dietary supplement products included Blackmores, Brand, MEGA, and Banner. The chose these brands due to its accepted standard quality. A criterion in selecting the product was mentioned to its reliable and neat package. They intentionally bought and decided to replace the finished product with the same product brand. They would buy a different brand after making attempt to find the needed one at different shops. In each time of purchase, the expense for tablet dietary supplement products was found at lower than 1,000 Baht. They also spent lower than 1,000 Baht for each type of tablet dietary supplement products. They bought it in according to the recommendation made by doctors and pharmacists. Online distribution channel via Internet or Social Network had not yet been popular among these consumers since the majority did not preferred buying it on the Internet. However, a little number of them did online-purchase as they felt convenient to do so. They did not have to arrange any transportation for their purchase and also felt easy to search for product information through the Internet. For those who denied buying the product via online channel, they revealed that they were not sure if the product was genuine and suspicious on the place of product distribution. Regarding the study on marketing mix factors affecting the decision of consumers towards buying tablet dietary supplement products in Mueang Chiang Mai district, the results presented that the consumers paid high level of importance on 4 marketing mix factors as follows. 1) Product factor affected their buying decision at high level and the highest level of importance was given to having the certified stamp from Food and Drug Administration. 2) Price factor affected their buying decision at high level and the highest level of importance was given to the reasonable price comparing to product’s mean quality. 3) Place factor affected their buying decision at high level and the highest level of importance was given to the image of product related to its reliability. 4) Promotion factor affected their buying decision at high level and the highest level of importance was given to the television advertisement. For problems and suggestions as obtained by interviewing with the respondents, the results suggested that most of them felt that for safe consumption, the purchase of tablet dietary supplement products should be done under the advises of doctors or pharmacists. For the highest benefits, the consumers should get to know the products by reading through its label to learn about ingredients, benefits, indications for a certain product and its limitations, as well as possible side-effects. They also agreed that if they were not sure of taking the product, they should consult with doctors and pharmacists. The government sectors should also keep control and examine all tablet dietary supplement products in the market, encourage consumers to consume the products with the certified stamp of Food and Drug Administration, and provide accessible news and information on tablet dietary supplement products to better the understanding of consumers.